Comparative microbial analysis and assessment of paired umbilical cord blood culture and peripheral venous blood culture in neonates with high risk factors to detect early onset neonatal sepsis: A study from tertiary care hospital of central India - Shukla, Gagandeep; Arya, Sunil; Goyal, Prachi; Channa, Urvashi (Asian Journal of Medical Sciences, 2022)
Background: Neonatal sepsis is a prime cause of neonatal morbidity and mortality. Peripheral venous blood (PVB) culture is a gold standard for the diagnosis of neonatal sepsis. Low sensitivity of blood culture in newborn is due to small volume of blood sample and antibiotics given before sampling. Aims and Objectives: The study aims to compare and analyze the microbial spectrum in the Umbilical cord blood (UCB) culture with PVB culture and evaluation of both for detection of early onset neonatal sepsis (EONS) in high risk neonates and to use appropriate microorganism specific antibiotic for treating the sepsis. Materials and Methods: About 100 inborn neonates with two or more risk factors for EONS, chosen by sequential sampling method were included in this prospective analytical study. Blood samples were collected from umbilical cord and peripheral vein for culture. Sepsis screen was done to substantiate the diagnosis of neonatal sepsis. Results: Out of 100 neonates, 21 belongs to sepsis; 14 to probable sepsis; 65 to no sepsis. Among these 27 had UCB culture & 24 had PVB culture +ve. Organisms grown on culture were Klebsiella(m/c isolate), Staphylococcus aureus, Escherichia coli, Acinetobacter, Coagulase-ve Staphylococcus (blood culture contaminant), Pseudomonas and Enterococcus. Conclusion: UCB culture is simple and convenient method for the diagnosis of neonatal sepsis as compared to PVB culture with Sensitivity of 66% and specificity of 93%. Organisms grown are comparable to PVB culture sample (Klebsiella - most common isolate).